Stories on Transcomplex Research: A New Integrative Approach (Agroindustria, Sociedad y Ambiente, 2021)
This essay propose some reflections on transcomplex research and its vision as a new integrative approach. It contains a short preamble to the research paradigms and their evolution in different historical periods. It starts from the analysis of the individual's critical capacity towards investigative praxis, and how epistemology influences the construction of scientific thinking that makes it contrast reality from a holistic and integrative perspective. From this perspective, the contributions of the positivist and interpretive paradigm oriented to the social sciences were investigated, and how transcomplex research analyzes the relevance of the methodological procedure of the research approaches typical of modernity and postmodernity. This allowed a new path for research to emerge, through an integrative approach; with the support that some researchers have called transepistemology, supported by different disciplines, which appeals to the crossed look of methods and the expanded integration of knowledge.
Keywords: Research; Transcomplexity; Epistemology